Electrochemical studies of carbon nanotubes, graphenes and layered nanomaterials - Wang, Lu (2016)
This thesis investigates the influence of impurities, doping and 3D structure on the properties of the nanocarbons and layered nanomaterials. The study mainly focusing on two objectives, a) Objective 1: Electrochemical studies on effects of impurities and doping of carbon nanotubes and graphenes, and b) Objective 2: Electrochemical studies on 3D layered nanomaterials. The thesis will begin by introducing the history and development of carbon nanotubes, graphenes and layered nanomaterials. Then the structures, fundamental properties and some electrochemical properties of the aforementioned nanomaterials were introduced. Later on, a literature review will be shown to reader for the recent development that relates to the objectives. After the introduction on recent progress that relates to the objectives, detailed results of the purposed objectives will be presented to reader. For objective 1, the effects of the carbonaceous impurities, metallic impurities and doping will be shown by varying different factors of the samples and indicate that both of the impurities and doping can influence the properties of the sample nanocarbons. In case of objective 2, the popular layered nanomaterials were coated/grown onto the 3D support and the electrochemical studies were performed and showing their electrocatalytic properties toward important reactions such as oxygen reduction reactions and hydrogen evolution reactions.